The Journal of Engineering Education-Its Journey from Issue No. 1 to No.75 and Beyond - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2006)
In June 1983, the Govt of Maharashtra adopted the policy of privatization for the Engineering Colleges and Polytechnics in the state of Maharashtra. Karnataka, Tamilnadu and Kerala had already taken this step much earlier.